MODELLING OF INDOOR/OUTDOOR LIGHTING FOR ENERGY HARVESTING IOT - RAPAIN, JORDAN (IRC, 2019)
The development of Internet of Things (IoT) has improved the daily lives of human when dealing with manual monitoring, agriculture automation and health care. One of the focus for the research related to IoT is how to develop sustainable power source with the continuous operation of wireless sensing nodes. Thus, energy harvesting system is very important to power up the IoT devices continuously because this system has the feature to harvest energy from the surrounding environment. This project focus on the modelling of Photovoltaic (PV) panel that can harvest indoor and outdoor lighting. The purpose of this project is to obtain real experimental data for the energy harvester and power management to the subsystem and to develop accurate models for each of the subsystems based on the experimental data. This project presents the methodology of the modelling of the PV panel with Improved Parameters Extraction Techniques (IPET) for indoor and outdoor lighting as well. Controlled experiment will be designed and executed to determine the performance of the PV panel model. Choosing the suitable power management board to be used in this project is also important to maximize the power harvested as well as to track the current and voltage from the PV panel. First experiment is to identify the value of irradiance at different illuminance. The second experiment is to obtain the value of current and voltage from the power management to the energy storage in 5 hours. The experimental result is compared with the modelled result to identify the accuracy as well as the performance of the model.